THE STUDY OF METHOD FOR SUPRESSING TRIPLEN HARMONIC PRODUCED BY SYNCHRONOUS GENERATOR - MD NOR, MUHAMMAD ARIF (Universiti Teknologi Petronas, 2011)
Harmonic can and often be found in generator. It is proved by the published journal that generator can produced harmonic. There are many types of generator such as synchronous generator and induction generator but this paper will only focus on synchronous generator. Third harmonic is being focus in this paper which gives the most influence in triplen harmonic magnitude that is produce by synchronous generator. The objective of this paper is to find alternatives to suppress triplen harmonic produce by synchronous generator. Besides, fundamental about triplen harmonic will be studied. The author also will try to model circuit by simulation. The cause and effect of harmonic to the generator also will be reviewed. There is already many ways to reduce triplen harmonic but it is not specifY for generator. So, this paper will apply all possible method to be implemented to the generator with hope that harmonic could be reduced. Method such as load variation, generator neutral earth resistance (NER), tuned Peterson coil and untuned Peterson coil method could suppress the triplen harmonic produced by synchronous generator. However, research show that delta configurations could not reduce triplen harmonic. Hope fully this research will help people in industrial business realize the cause and effect of harmonic and help them to reduce triplen harmonic produce by their generator.